2011
DOI: 10.1038/modpathol.2010.236
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CASR expression and global loss of parafibromin staining are strong negative determinants of prognosis in parathyroid carcinoma

Abstract: Parathyroid carcinoma is associated with mutations in the HRPT2/CDC73 gene and with decreased parafibromin and calcium-sensing receptor (CASR) expression, but in some cases establishing an unequivocal diagnosis remains a challenge. The aim of our study was to evaluate the prognostic value of CASR and parafibromin expression and of HRPT2/CDC73 mutations in patients with an established diagnosis of parathyroid carcinoma. Data on survival and disease-free survival were obtained from hospital records of 23 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 30 publications
4
54
1
Order By: Relevance
“…54 Wittveen et al have also showed that the loss of parafibromin, either alone or in combination with CDC73 mutations and down-regulation of the calcium sensing receptor expression, has a negative impact on the survival rate in patients with parathyroid cancer. 70 Based on these data, we suggest that abnormalities of the CDC73 gene should be investigated not only for diagnostic purposes in tumors with uncertain diagnosis of malignancy but also in unequivocal cancers, because of their prognostic value. Moreover, the CDC73 mutational analysis would permit the identification of patients carrying a germline mutation and prompt an extension of the genetic analysis to first-degree relatives.…”
Section: Newer Adjuncts To Pathological Diagnosismentioning
confidence: 96%
See 1 more Smart Citation
“…54 Wittveen et al have also showed that the loss of parafibromin, either alone or in combination with CDC73 mutations and down-regulation of the calcium sensing receptor expression, has a negative impact on the survival rate in patients with parathyroid cancer. 70 Based on these data, we suggest that abnormalities of the CDC73 gene should be investigated not only for diagnostic purposes in tumors with uncertain diagnosis of malignancy but also in unequivocal cancers, because of their prognostic value. Moreover, the CDC73 mutational analysis would permit the identification of patients carrying a germline mutation and prompt an extension of the genetic analysis to first-degree relatives.…”
Section: Newer Adjuncts To Pathological Diagnosismentioning
confidence: 96%
“…Diffuse or focal loss of nuclear parafibromin expression by immunohistochemistry has been found in the majority of parathyroid carcinomas but very rarely in parathyroid adenomas. 49,51,52,[64][65][66][67][68][69][70] A recent genome-wide study of DNA methylome from benign and malignant parathyroid tumors identified a number of genes with altered DNA methylation patterns independent of the tumor's nature, suggesting that other genes are involved in parathyroid carcinogenesis. 71 Costa-Guda et al have recently shown that allelic loss at chromosome 11q, the most common alteration in parathyroid adenomas, has never been detected in parathyroid cancers, suggesting that parathyroid malignancy arises de novo, rather than evolving from a pre-existing benign lesion.…”
Section: Pathogenesismentioning
confidence: 99%
“…Cetani et al [18] has identified germline CDC73 mutations in two patients with sporadic parathyroid cancer. The presence of CDC73 mutations was associated with sevenfold increased risk of developing local or distant metastasis [20]. Identification of CDC73 mutation not only assists in establishing a diagnosis of parathyroid carcinoma, but also has significant prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HRPT2/CDC73 mutations, Witteveen et al reported a seven-fold increased risk of developing local or distant metastasis. All four patients with the gene mutation developed local recurrence and/or distant metastasis, which occurred only in 10 of 19 patients without mutations [53]. Wang et al did not find a significant correlation between a mutation in HRPT2/CDC73 and distant metastases but did find a higher incidence of recurrence in patients with HRPT2/CDC73 mutations (100% vs. 50%, p = 0.031), after adjusting for gender, age, initial serum calcium and duration of follow-up [51].…”
Section: Discussionmentioning
confidence: 99%